2020
DOI: 10.1186/s13071-020-04147-6
|View full text |Cite|
|
Sign up to set email alerts
|

Detection of gastrointestinal parasitism at recreational canine sites in the USA: the DOGPARCS study

Abstract: Background: The rapid growth in off-leash dog parks provides opportunity for canine socialization activities but carries risk of exposure to intestinal parasites. This study assessed the prevalence of these infections in dogs visiting off-leash dog parks. Methods: Fresh defecations were collected from dogs visiting parks in 30 metropolitan areas across the USA. Samples were analyzed by coproantigen immunoassay (CAI) (Fecal Dx ® and Giardia Test, IDEXX Laboratories, Inc.) and zinc sulfate centrifugal flotation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 31 publications
(56 reference statements)
7
44
0
Order By: Relevance
“…Companion animals are frequent carriers of both symptomatic and asymptomatic Giardia infections ( Figure 1 ; Tysnes et al, 2014 ; Bouzid et al, 2015 ; Stafford et al, 2020 ). The prevalence of giardiasis varies widely by region but has been estimated via meta-analysis of prevalence reports to be approximately 15% in dogs and 12% in cats ( Bouzid et al, 2015 ).…”
Section: Alterations To the Microbiota During Giardia mentioning
confidence: 99%
“…Companion animals are frequent carriers of both symptomatic and asymptomatic Giardia infections ( Figure 1 ; Tysnes et al, 2014 ; Bouzid et al, 2015 ; Stafford et al, 2020 ). The prevalence of giardiasis varies widely by region but has been estimated via meta-analysis of prevalence reports to be approximately 15% in dogs and 12% in cats ( Bouzid et al, 2015 ).…”
Section: Alterations To the Microbiota During Giardia mentioning
confidence: 99%
“…Studies evaluating feline fecal samples have reported the prevalence of Cystoisospora and Giardia to range between 3.8–26.0% and 1.2–9.9%, respectively, with the highest prevalence in shelter cats [ 3 , 5 8 , 19 , 20 , 24 , 25 ]. The prevalence of Cystoisospora and Giardia in dogs has been reported to range between 0.5–10.4% and 3.3–13%, respectively [ 8 , 19 , 21 – 24 , 26 – 31 ]. Cystoisospora oocysts and Giardia cysts/trophozoites are small in size and can be challenging to detect by microscopy, especially when fecal samples contain a low number of oocysts, cysts, or trophozoites.…”
Section: Introductionmentioning
confidence: 99%
“…Studies evaluating feline fecal samples have reported the prevalence of Cystoisospora and Giardia to range between 3.8-26.0% and 1.2-9.9%, respectively, with the highest prevalence in shelter cats [3-7, 18, 19, 21, 24]. The prevalence of Cystoisospora and Giardia in dogs has been reported to range between 0.5-10.4% and 3.3-13%, respectively [4,[19][20][21][22][23][25][26][27][28][29][30]. Cystoisospora oocysts and Giardia cysts/trophozoites are small in size and can be challenging to detect by microscopy, especially when fecal samples contain a low number of oocysts, cysts, or trophozoites.…”
Section: Introductionmentioning
confidence: 99%